2018
DOI: 10.1021/acssuschemeng.8b01452
|View full text |Cite
|
Sign up to set email alerts
|

Free Ammonia-Based Pretreatment Promotes Short-Chain Fatty Acid Production from Waste Activated Sludge

Abstract: This work reports a new waste activated sludge (WAS) pretreatment method based on free ammonia (FA) for promoting the generation of short-chain fatty acids (SCFAs). Experimental results showed that pretreatment of WAS for 3 days with FA largely improved WAS disintegration, with the highest dissolution (soluble chemical oxygen demand (COD), 3400 ± 120 mg/L at initial FA level of 237.8 mg/L) being 4.5-fold that without FA pretreatment. The pretreatment method by FA facilitated the breakdown of extracellular poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 49 publications
(85 reference statements)
2
41
0
Order By: Relevance
“…In recent years, some researchers have proposed a new strategy to increase bioenergy recovery from wastewater or sludge treatment using FA. [15][16][17][18] They demonstrate that pre-treatment of the activated sludge with FA for 24-40 h could reduce sludge yields by 20%. At the same time, the NOB activity could be decreased to some extent without any adverse impact on the reactor performance.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some researchers have proposed a new strategy to increase bioenergy recovery from wastewater or sludge treatment using FA. [15][16][17][18] They demonstrate that pre-treatment of the activated sludge with FA for 24-40 h could reduce sludge yields by 20%. At the same time, the NOB activity could be decreased to some extent without any adverse impact on the reactor performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study also showed that 40 mg FA/L posed 80% inhibition to the activity of methanogens (Mccarty and Mckinney, 1961). When 178.4 mg FA/L was applied to pretreat sludge 3 d, the maximum SCFA production (267.2 mg COD/g VSS) was achieved at fermentation time of 8 d, which was 3.2-fold of that from the control (without FA pretreatment) (Zhang et al, 2018). Although FA was an effective and validated pretreatment method with significant contribution, the maximal SCFA production required long fermentation time (8 d) and more than 60% of VSS could not be degraded during anaerobic fermentation, which inevitably, to some extent, weakens the its values, hindering its further application in real-world situations.…”
Section: Introductionmentioning
confidence: 92%
“…SCFA are a subset of saturated fatty acids with six or less carbon molecules (e.g., acetate, propionate, and butyrate). These are produced by acidogenesis, acetogenesis, and homoacetogenes bacterial processes (Zhang et al, ). Besides, SCFA may be further re‐captured for energy recovery which might later be used as a raw substrate for other microorganism reactions (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These are produced by acidogenesis, acetogenesis, and homoacetogenes bacterial processes (Zhang et al, 2018). Besides, SCFA may be further re-captured for energy recovery which might later be used as a raw substrate for other microorganism reactions .…”
mentioning
confidence: 99%